Ex-situ conservation of the native orchid Coelogyne rochussenii de Vriese from the Bukit Rimbang and Baling Wildlife Reserve Areas - Pebra Heriansyah; Gusti Marlina (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2021)
The native orchid Coelogyne rochussenii de Vriese is critically endangered, hence, conservative measures are needed to prevent extinction. Meanwhile, in-situ conservation is constrained by time, resources, and costs. Therefore, this study aims to identify the most effective method for ex-situ conservation, especially with basal medium and activated charcoal, to determine the fastest germination. The completely randomized factorial design of four different basal media treatments including Knudson C, Vacin and Went, Murashige and Skoog, and Hyponex + vitamin medium were used. These treatments were combined with the application of activated charcoal at four different levels, with concentrations of 0, 1, 2, and 3 g/L-1, meanwhile, the parameters observed include germination day and percentage, as well as contamination percentage. The results showed that the conservation of Native orchid C. rochussenii de Vriese using various growing media and activated charcoal had a significant effect on the growth of the embryo culture. Based on the results, the Hyponex + vitamin medium with 3 g/L-1 accelerated germination days to 29.33, increased germination percentage to 92.06%, and reduced contamination to 0%.